2003
DOI: 10.3402/tellusb.v55i1.16355
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the loss of snow-deposited MSA to the interstitial gaseous phase in central Antarctic firn

Abstract: We have examined several MSA (methanesulfonic acid) records from the upper 200 m of the Antarctic ice sheet and in particular the new Dome F profile. At all the four sites studied, concentration profiles exhibit similar patterns as a function of depth. They suggest that snow metamorphism and solid phase migration are responsible for a marked release of gaseous MSA to interstitial firn air as well as probably to the free atmosphere, in particular at extremely low accumulation sites. Snow acidity can also modify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…[] suggested that minima of nssSO 4 2− in the 1999 DF pit were formed in summer by sublimation‐condensation of water vapor between near‐surface snow and the atmosphere. Moreover, some studies have suggested that MSA maxima could move from summer to winter at high latitudes as a result of postdepositional modification [ Curran et al ., ; Delmas et al ., ]. This process involves removal of gaseous MSA from the snow layers and its return to the free atmosphere, where it may be partly redeposited in the snow layers or remains in the interstitial air [ Delmas et al ., ].…”
Section: Discussionsupporting
confidence: 59%
“…[] suggested that minima of nssSO 4 2− in the 1999 DF pit were formed in summer by sublimation‐condensation of water vapor between near‐surface snow and the atmosphere. Moreover, some studies have suggested that MSA maxima could move from summer to winter at high latitudes as a result of postdepositional modification [ Curran et al ., ; Delmas et al ., ]. This process involves removal of gaseous MSA from the snow layers and its return to the free atmosphere, where it may be partly redeposited in the snow layers or remains in the interstitial air [ Delmas et al ., ].…”
Section: Discussionsupporting
confidence: 59%
“…However, the interpretation of MSA signals in ice cores is still ambiguous. This is due to the highly complex mechanisms controlling DMS emission from algae [ Andreae , 1990; Saltzman , 1995; Simó and Pedrós‐Alió , 1999; Simó and Dachs , 2002; Toole and Siegel , 2004], variable MSA yields from DMS photo‐oxidation [ Ayers et al , 1996; Koga and Tanaka , 1999; Gondwe et al , 2004], and finally post depositional losses and migration of MSA signals within annual firn layers [ Minikin et al , 1994; Pasteur and Mulvaney , 2000; Delmas et al , 2003; Weller et al , 2004].…”
Section: Introductionmentioning
confidence: 99%
“…This in principle holds for MS − as well and has been clearly observed for seasonally high acid layers in ice cores from the Filchner‐Ronne ice shelf [ Minikin et al , 1994]. In addition, ice core studies at Vostok showed decreasing MS − concentrations in the top layers and very low concentrations in the upper 50 m that have been attributed to a net loss of MS − from the firn column as well as loss due to improper storage [ Delmas et al , 2003].…”
Section: Introductionmentioning
confidence: 68%
“…As clearly shown [ Curran et al , 2002; Delmas et al , 2003; Legrand et al , 1996; Wagnon et al , 1999; Weller et al , 2004] MS − records are subject to diffusional smoothing and postdepositional net loss in the firn column, the latter being strongly dependent on snow accumulation rate. Because the snow accumulation in the past has been reconstructed in our ice cores a correction for loss process is in principle possible (e.g., according to Weller et al [2004]).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation